Preferences for Modes, Residential Location and Travel Behaviour: the Relevance for Land-Use Impacts on Mobility - van Wee, Bert; Holwerda, Hans; van Baren, Rick (European Journal of Transport and Infrastructure Research, 2002)
Nowadays almost all researchers focusing on the impact of land use on travel behaviour examine personal and household variables such as income, age and household type. Still, within ‘homogeneous’ groups there may be preferences for travel modes (especially car or public transport), and these may have an impact on the influence of land use on travel behaviour − a subject for which available literature is scarce. This paper represents then an endeavour to relay results of empirical research on this matter and also attempts to answer the following questions: 1. Are there preferences for modes? 2. Is there a relationship between preferences and neighbourhood characteristics? 3. Have preferences for modes played a role in residential choices of households? 4. Do preferences for modes add explanatory power to models for travel behaviour that include personal and household characteristics, and land-use variables? Results obtained reveal positive answers to all four questions; but this then confronts us with the following question: Do land-use policies then make no sense? Yes, in our opinion, these policies certainly do make sense, in the least because they allow people who prefer certain modes to live in an area that meets their preferences. However, this does not mean that land-use alternatives leading to the lowest car use levels should always be recommended. Rather, what is needed is a broad evaluation of all the pros and cons of these alternatives.